Eastern Europe as a blind spot in the research assessment reform (PUBMET, 2025)
Many Eastern European research institutions and organizations have joined the Coalition on Advancing Research Assessment, an international effort aimed at reforming how research is evaluated, including a move away from the crude use of metrics and rankings.